Overview of Conversation according to Erving Goffman - Cano, Álvaro (Disertaciones, 2019)
If we start from an intuitive definition, conversation has been understood as a kind of verbal communicative behavior determine by a specific system of turn taking, mediate by the interest and pourposes of the comunicative exchange. This brings fort some theorethical consecuencies aproached by the autor which will be tracked in this bibliographical guide about the analises of conversation emphazising the turn takes. This list is a result of a prolongued lecture of diverse documents and autors, allowing me to arrange a useful presentation for those intrested in this topics.The first part is dedicatted to an overview of the different tendecies and scholars of this topic, to offer a brief overview of the theoretical envirioment where appears the question about the conversation. Then, in the second part, will be sinthetized the main ideas of the autor about conversational analysis and its alegorial realtions with theatre, trying to expose the main ideas of this canadian sociolinguicist, who has developed his work in EE.UU., especially in his book The Presentation of Self in Everyday Life (1982), then will be exhibited the main steps of Goffman`s research based on theatral experience.
Keywords: Sociolinguistics; Conversation; Turn Taking; Theatre